Laminated film
By forming an inorganic film layer on the semi-aromatic polyamide substrate of the LED display panel, the problems of yellowing and dimensional changes of the substrate at high temperature are solved, and high thermal stability and position stability are achieved, which are suitable for applications such as LED display panels.
Patent Information
- Application Number
- JP2024116763
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2024-07-22
- Publication Date
- 2025-02-05
AI Technical Summary
The substrates of existing LED display panels are prone to yellowing at high temperatures and lack thermal stability, resulting in large size changes, making it difficult to meet the needs of LED displays.
Semi-aromatic polyamide is used as a substrate, and an inorganic film layer is formed thereon, forming a multi-layer structure to improve thermal stability and dimensional stability, including an inorganic film layer on both sides or one side of the substrate, and preparing an inorganic film by vacuum evaporation and other methods.
It significantly suppresses yellowing at high temperatures, improves thermal stability and dimensional stability, and is suitable for applications such as LED display panels, ensuring that it is not easy to deform and stable in high temperatures.
Smart Images

Figure 2025017345000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate film having a substrate film and an inorganic thin film layer. [Background technology]
[0002] In recent years, LED displays using light-emitting diode (LED) elements and organic electroluminescence (EL) displays using organic EL elements have come into practical use. Conventionally, glass substrates have been used for mounting elements, but there is a demand for thinner, lighter, and more flexible substrates, and the use of resin film substrates is being considered. LED substrates are required to have high heat resistance so that they can withstand high temperatures during soldering of LED elements and during LED light emission. They are also required to have a low thermal shrinkage rate so that they are less likely to change in size even at high temperatures. From this perspective, the use of semi-aromatic polyamide films as materials for LED substrates has been considered, and for example, Patent Document 1 discloses a semi-aromatic polyamide film that can be suitably used as a substrate for display materials. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2020 / 230806 Summary of the Invention [Problem to be solved by the invention]
[0004] After circuits are formed on the LED substrate, the substrate film must be able to withstand soldering and must have heat resistance that suppresses yellowing after heat treatment. An object of the present invention is to provide a film that can be used as an LED mounting substrate and has excellent heat resistance (hereinafter, simply referred to as "heat resistance") and is inhibited from yellowing after heat treatment. [Means for solving the problem]
[0005] As a result of extensive research into solving the above problems, the present inventors have found that a laminate film having a specific inorganic thin film layer can solve the above problems, and have thus completed the present invention. That is, the gist of the present invention is as follows.
[0006] (1) A laminate film having at least a substrate film (X) and an inorganic thin film layer (Y), The base film (X) is a semi-aromatic polyamide film, Yellowness (YI) when heat treated at 250℃ for 5 minutes B ) is less than or equal to 5.50, Yellowness before heat treatment (YI A Yellowing index (YI) is expressed as a ratio to the B / YI A ) is 1.60 or less. (2) The laminate film according to (1), characterized in that the moisture absorption elongation in the longitudinal direction and the moisture absorption elongation in the transverse direction of the laminate film, measured when the humidity environment is changed from 23°C x 50% RH to 23°C x 90% RH, are each 0.2% or less. (3) The water vapor permeability of the laminated film at 40°C x 90% RH measured in accordance with JIS K7129-1 is 5.5g / (m 2 The laminate film according to (1) or (2), characterized in that: d) is equal to or less than the above. (4) The laminate film according to (1) or (2), characterized in that it has an inorganic thin film layer (Y) on a first surface side of the base film (X) and also has an inorganic thin film layer (Y) on a second surface side of the base film (X). (5) The laminate film according to (1) or (2), wherein the semi-aromatic polyamide film is biaxially oriented. (6) The laminate film according to (1) or (2), wherein the substrate film (X) and the inorganic thin film layer (Y) are adjacent to each other. (7) A copper-clad laminate comprising the laminate film described in (1) or (2) above. (8) An LED mounting substrate using the laminate film described in (1) or (2) above. (9) An LED display using the LED mounting board described in (8) above. Effect of the Invention
[0007] Since the laminated film of the present invention has excellent heat resistance, it can be suitably used as an LED mounting substrate for a flexible LED display, an optical substrate for an organic EL display, an electronic substrate material such as a flexible printed wiring board or a flexible flat cable, a coverlay film for a flexible printed wiring board, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in detail below. The laminated film of the present invention is a laminated film having at least a base film (X) and an inorganic thin film layer (Y). The base film (X) is a semi-aromatic polyamide film. The laminated film has a yellowness index (YI) of 1.0 or less when heat-treated at 250° C. for 5 minutes. B ) is 5.50 or less, and the yellowness index (YI) before heat treatment is A Yellowing index (YI) is expressed as a ratio to the B / YI A ) is less than or equal to 1.60.
[0009] <Base film (X)> The base film (X) constituting the laminated film of the present invention is a semi-aromatic polyamide film. Semi-aromatic polyamides have an excellent balance of mechanical properties such as heat resistance and bending resistance, and films formed from semi-aromatic polyamides have transparency.
[0010] (Semi-aromatic polyamide) In the present invention, the semi-aromatic polyamide constituting the semi-aromatic polyamide film is composed of a dicarboxylic acid component and a diamine component, and has an aromatic component in the dicarboxylic acid component or the diamine component.
[0011] The dicarboxylic acid component constituting the semi-aromatic polyamide preferably contains terephthalic acid as a main component, and the proportion of terephthalic acid in the dicarboxylic acid component is preferably 60 to 100 mol %. Examples of the dicarboxylic acid component other than terephthalic acid include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, and octadecanedioic acid, and aromatic dicarboxylic acids such as 1,4-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,2-naphthalenedicarboxylic acid, and isophthalic acid.
[0012] The diamine component constituting the semi-aromatic polyamide preferably contains as a main component an aliphatic diamine having a carbon number of 4 to 15. The proportion of the aliphatic diamine having a carbon number of 4 to 15 in the diamine component is preferably 60 to 100 mol %. Examples of the aliphatic diamine having 4 to 15 carbon atoms include 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,14-tetradecanediamine, 1,15-pentadecanediamine, etc. These may be used alone or in combination of two or more kinds.
[0013] As the semi-aromatic polyamide, a semi-aromatic polyamide consisting of a dicarboxylic acid component consisting only of terephthalic acid (100 mol % terephthalic acid) and a diamine component containing 1,9-nonanediamine and 2-methyl-1,8-octanediamine in a total amount of 60 to 100 mol % in the diamine component, or a semi-aromatic polyamide consisting of a dicarboxylic acid component consisting only of terephthalic acid (100 mol % terephthalic acid) and a diamine component containing 1,10-decanediamine is preferable.
[0014] In the semi-aromatic polyamide, lactams such as ε-caprolactam, ζ-enantholactam, η-capryllactam, ω-laurolactam, etc. may be copolymerized within the scope of the present invention.
[0015] The type and copolymerization ratio of the monomers constituting the semi-aromatic polyamide are preferably selected so that the melting point (Tm) of the resulting semi-aromatic polyamide is in the range of 270 to 350°C. When the Tm of the semi-aromatic polyamide is in the above range, thermal decomposition during processing into a film can be efficiently suppressed. If the Tm is less than 270°C, the heat resistance of the resulting film may be insufficient. On the other hand, if the Tm exceeds 350°C, thermal decomposition may occur during film production.
[0016] The semi-aromatic polyamide preferably has an intrinsic viscosity of 0.8 to 2.0 dL / g, more preferably 0.9 to 1.8 dL / g. When the semi-aromatic polyamide has an intrinsic viscosity of 0.8 dL / g or more, a film having excellent mechanical strength can be produced, but when the intrinsic viscosity exceeds 2.0 dL / g, it may be difficult to produce the film.
[0017] The semi-aromatic polyamide may contain a polymerization catalyst and an end-capping agent. Examples of the end-capping agent include acetic acid, lauric acid, benzoic acid, octylamine, cyclohexylamine, and aniline. Examples of the polymerization catalyst include phosphoric acid, phosphorous acid, hypophosphorous acid, and salts thereof.
[0018] (Semi-aromatic polyamide film) The semi-aromatic polyamide film constituting the laminated film of the present invention preferably has a thickness of 20 μm or more, more preferably 30 μm or more, and even more preferably 50 μm or more. By having a thickness of 20 μm or more, the semi-aromatic polyamide film can prevent the entire laminate from warping when an LED element is mounted. The semi-aromatic polyamide film preferably has a thickness of 200 μm or less, more preferably 160 μm or less, and even more preferably 90 μm or less. The semi-aromatic polyamide film having a thickness of 200 μm or less makes it easy to handle in roll-to-roll processing, and when applied to an LED mounting board, it is possible to suppress an increase in the overall thickness of the LED mounting board.
[0019] The semi-aromatic polyamide film is preferably at least uniaxially oriented, more preferably biaxially oriented.
[0020] The semi-aromatic polyamide film may be a single-layer film consisting of one type of layer, or may be a multi-layer structure consisting of two or more layers laminated together. In the case of a multi-layer structure, for example, a lubricant may be contained in any one of the two layers in a two-layer film, and a lubricant may be contained in each of the layers located on both surfaces in a three-layer film. The type and content of the lubricant to be contained can be designed independently. By forming such a multi-layer structure, the surface roughness of each surface of the semi-aromatic polyamide film can be controlled independently.
[0021] The surface of the semi-aromatic polyamide film may be laminated with an adhesive layer or may be subjected to corona treatment, plasma treatment, acid treatment, flame treatment, or the like in order to improve adhesion to other materials.
[0022] The semi-aromatic polyamide film may be laminated with a layer made of an inorganic material such as a metal or its oxide other than the inorganic thin film layer (Y), a layer made of other types of polymers, a layer made of paper, a woven fabric, a nonwoven fabric, a layer made of wood, or the like.
[0023] The semi-aromatic polyamide film may contain fine particles for the purpose of improving slipperiness, etc. In the semi-aromatic polyamide film, either inorganic fine particles or organic fine particles can be used as the fine particles.
[0024] Examples of inorganic fine particles contained in the semi-aromatic polyamide film include fine particles of silica, alumina, titanium dioxide, calcium carbonate, kaolin, barium sulfate, etc. Examples of organic fine particles include acrylic resin particles, melamine resin particles, silicone resin particles, crosslinked polystyrene particles, etc. Among these, silica fine particles and acrylic resin particles are preferred in terms of good dispersibility and ease of handling in the film. The average particle size of the fine particles is preferably 0.05 to 5.0 μm, and more preferably 0.1 to 4.0 μm. The content of the fine particles is preferably 0 to 0.2% by mass, more preferably 0.01 to 0.2% by mass, and further preferably 0.02 to 0.1% by mass. In addition, when the content of the fine particles having an average particle size of 0.05 to 2.0 μm is 0.2 mass% or less, and when the content of the fine particles having an average particle size of 2.1 to 5.0 μm is 0.1 mass% or less, the slipperiness of the film can be efficiently improved. In addition, two or more kinds of fine particles having different average particle sizes can be used in combination. As described above, the average particle size and content of the fine particles can be selected depending on the frictional properties, optical properties, and other properties required for the film, and the fine particles can be added within a range that does not impair transparency.
[0025] In addition to the fine particles, the semi-aromatic polyamide film may contain additives such as lubricants, colorants such as pigments or dyes such as titanium, color inhibitors, heat stabilizers, hindered phenols, antioxidants such as phosphates and phosphites, weather resistance improvers such as benzotriazole-based compounds, bromine-based and phosphorus-based flame retardants, plasticizers, release agents, reinforcing agents such as talc, modifiers, antistatic agents, ultraviolet absorbers, anti-fogging agents, and various polymer resins, as necessary.
[0026] Various methods can be used to incorporate the above-mentioned fine particles and additives into the film. Representative methods include the following. (A) Method of adding during polymerization of semi-aromatic polyamide (B) A method in which a masterbatch pellet is prepared by directly adding the compound to a semi-aromatic polyamide and melt-kneading the masterbatch pellet, and the masterbatch pellet is added during film formation and melt-kneaded in an extruder. (C) Direct addition to semi-aromatic polyamide during film production and melt kneading in an extruder (D) Direct addition to the extruder during film production and melt kneading
[0027] (Method of manufacturing semi-aromatic polyamide film) The method for producing the semi-aromatic polyamide film constituting the laminated film of the present invention is not particularly limited, but it can be produced, for example, by the following method.
[0028] As the semi-aromatic polyamide for producing the semi-aromatic polyamide film, commercially available products can be suitably used, such as "Genesta (registered trademark)" manufactured by Kuraray Co., Ltd., "Zecot (registered trademark)" manufactured by Unitika Ltd., "Reny (registered trademark)" manufactured by Mitsubishi Engineering Plastics Corporation, "Arlen (registered trademark)" manufactured by Mitsui Chemicals, Inc., "Ultramid (registered trademark)" manufactured by BASF, and Nylon MXD6 manufactured by Mitsubishi Gas Chemical Company, Inc.
[0029] Semi-aromatic polyamides can be produced by using a method known as a method for producing crystalline polyamides. For example, there can be mentioned a solution polymerization method or an interfacial polymerization method (Method A) using an acid chloride and a diamine component as raw materials, a method (Method B) in which a low polymer is produced using a dicarboxylic acid component and a diamine component as raw materials, and the low polymer is polymerized by melt polymerization or solid-phase polymerization, a method (Method C) in which a crushed mixture of salt and low polymer is produced using a dicarboxylic acid component and a diamine component as raw materials, and the mixture is solid-phase polymerized, and a method (Method D) in which a salt is produced using a dicarboxylic acid component and a diamine component as raw materials, and the mixture is solid-phase polymerized. Among them, Methods C and D are preferred, and Method D is more preferred. Methods C and D can produce a crushed mixture of salt and low polymer or salt at a lower temperature than Method B, and do not require a large amount of water when producing a crushed mixture of salt and low polymer or salt. Therefore, the generation of gel-like bodies can be reduced, and fish eyes can be reduced.
[0030] In the B method, for example, a nylon salt prepared by mixing a diamine component, a dicarboxylic acid component, and a polymerization catalyst all at once is heated and polymerized at a temperature of 200 to 250°C to obtain a low polymer. The intrinsic viscosity of the low polymer is preferably 0.1 to 0.6 dL / g. By setting the intrinsic viscosity of the low polymer in this range, there is an advantage that the polymerization rate can be increased without causing a collapse of the molar balance of the carboxyl group in the dicarboxylic acid component and the amino group in the diamine component in the subsequent solid-phase polymerization or melt polymerization. If the intrinsic viscosity of the low polymer is less than 0.1 dL / g, the polymerization time may be long, resulting in poor productivity. On the other hand, if it exceeds 0.6 dL / g, the obtained semi-aromatic polyamide may be colored. The solid-state polymerization of the low polymer is preferably carried out under reduced pressure or in an inert gas flow. The temperature of the solid-state polymerization is preferably 200 to 280°C. By setting the temperature of the solid-state polymerization within this range, coloration and gelation of the obtained semi-aromatic polyamide can be suppressed. If the temperature of the solid-state polymerization is less than 200°C, the polymerization time becomes long, which may result in poor productivity. On the other hand, if the temperature exceeds 280°C, coloration and gelation may occur in the obtained semi-aromatic polyamide. The melt polymerization of the oligomer is preferably carried out at a temperature of 350° C. or less. If the polymerization temperature exceeds 350° C., decomposition or thermal deterioration of the semi-aromatic polyamide may be accelerated. Therefore, the film obtained from such a semi-aromatic polyamide may have poor strength and appearance. The above melt polymerization also includes melt polymerization using a melt extruder.
[0031] In the C method, for example, a suspension of molten aliphatic diamine and solid aromatic dicarboxylic acid is stirred and mixed to obtain a mixed liquid. Then, in this mixed liquid, a reaction of aromatic dicarboxylic acid and aliphatic diamine to produce a salt and a reaction of the produced salt to produce a low polymer are carried out at a temperature below the melting point of the semi-aromatic polyamide to be finally produced, to obtain a mixture of salt and low polymer. In this case, crushing may be carried out while the reaction is carried out, or the reaction may be taken out once after the reaction and then crushed. Then, the obtained reaction product is solid-phase polymerized at a temperature below the melting point of the semi-aromatic polyamide to be finally produced, and the molecular weight is increased to a predetermined molecular weight, to obtain a semi-aromatic polyamide. The solid-phase polymerization is preferably carried out in an inert gas stream such as nitrogen at a polymerization temperature of 180 to 270°C and a reaction time of 0.5 to 10 hours.
[0032] In the D method, for example, aromatic dicarboxylic acid powder is heated in advance to a temperature equal to or higher than the melting point of the aliphatic diamine and equal to or lower than the melting point of the aromatic dicarboxylic acid, and an aliphatic diamine is added to the aromatic dicarboxylic acid powder at this temperature without substantially containing water so as to maintain the state of the aromatic dicarboxylic acid powder, thereby preparing a salt. The obtained salt is then solid-phase polymerized at a temperature lower than the melting point of the semi-aromatic polyamide to be finally produced, and the molecular weight is increased to a predetermined molecular weight, thereby obtaining a semi-aromatic polyamide. The solid-phase polymerization is preferably carried out in an inert gas stream such as nitrogen, at a polymerization temperature of 180 to 270°C and a reaction time of 0.5 to 10 hours.
[0033] The raw material for the semi-aromatic polyamide film may be a mixture of the above virgin raw materials, or may be a mixture of non-standard films or scraps generated as edge trimmings during the production of the semi-aromatic polyamide film, or may be a mixture of the scrap mixture and virgin raw materials. These mixtures may be performed by known methods such as a dry blending method using a known device, or a kneading method in which the materials are melt-kneaded and mixed using a single-screw or twin-screw extruder.
[0034] In the method for producing a semi-aromatic polyamide film, the unstretched film of semi-aromatic polyamide resin used in the stretching step can be produced by melt-mixing the semi-aromatic polyamide resin in an extruder at a temperature of 280 to 340°C for 3 to 15 minutes, extruding the resin into a sheet through a T-die, and cooling the sheet by placing it in close contact with a cooling roll whose temperature is adjusted to 30 to 40°C.
[0035] In the method for producing a semi-aromatic polyamide film, the unstretched film is preferably stretched at least uniaxially, more preferably biaxially. The stretching causes the semi-aromatic polyamide resin to be oriented and crystallized. From the viewpoint of the oriented crystallization of the resin, the sequential biaxial stretching method is optimal. The stretching method is not particularly limited, and may be a flat-type sequential biaxial stretching method, a flat-type simultaneous biaxial stretching method, a tubular method, etc. Among them, the flat-type sequential biaxial stretching method and the flat-type simultaneous biaxial stretching method are preferred because they can provide a film with good thickness accuracy. Examples of the stretching device for employing the flat-type simultaneous biaxial stretching method include a screw-type tenter, a pantograph-type tenter, and a linear motor-driven clip-type tenter.
[0036] In the semi-aromatic polyamide film of the present invention, the higher the residual stress, the higher the moisture absorption dimensional stability, but the lower the thermal dimensional stability. Therefore, it is important to produce the film by adjusting the conditions shown below, such as the stretching conditions and heat setting conditions, so as to achieve a balance between the moisture absorption dimensional stability and the thermal dimensional stability.
[0037] The stretching ratio is preferably 2.0 to 3.5 times in the machine direction (MD) and 2.0 to 4.0 times in the transverse direction (TD), and more preferably 2.5 to 3.5 times in the machine direction and 3.0 to 4.0 times in the transverse direction. If the stretching ratio in the longitudinal direction exceeds 3.5 times, the obtained stretched film may be crystallized too much, and the stretchability in the width direction may decrease. Even if the stretching in the width direction is possible, the obtained stretched film is likely to have stretching unevenness, and the thickness accuracy, the tensile strength in the longitudinal direction, and the transparency may decrease. On the other hand, if the stretching ratio in the transverse direction exceeds 4.0 times, the transparency decreases, the heat shrinkage rate increases, the dimensional stability decreases, and further the tensile strength may decrease. If the stretching ratio in the longitudinal direction and the transverse direction is less than 2.0 times, stretching unevenness is likely to occur, which may result in uneven thickness and reduced flatness.
[0038] The stretching speed is preferably such that the stretching strain rate in both the longitudinal direction and the transverse direction exceeds 400% / min, more preferably 800 to 12000% / min, and even more preferably 1200 to 6000% / min. If the strain rate is 400% / min or less, crystals may grow during stretching, causing the film to break. Conversely, if the strain rate is too fast, the unstretched film may be unable to keep up with the deformation and break. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the semi-aromatic polyamide resin, and more preferably exceeds Tg and is equal to or lower than (Tg+50° C.). If the stretching temperature is lower than Tg, the film is prone to breakage and stable production cannot be performed, whereas if the stretching temperature exceeds (Tg+50° C.), stretching unevenness may occur in the film.
[0039] After the above-mentioned stretching, the semi-aromatic polyamide film is preferably heat-set while the film is held by the clips used for stretching. By performing heat-set, the obtained film can have a reduced heat shrinkage without heat-induced spots. The heat-set temperature is preferably 260 to 280°C, more preferably 263 to 278°C, and even more preferably 265 to 275°C. If the heat-set temperature is less than 260°C, the obtained film has a high heat shrinkage. If the heat-set temperature exceeds 280°C, the obtained film has a reduced tensile strength and is prone to poor appearance due to heat-induced wrinkles, and in some cases breaks during heat-set, making it difficult to obtain a biaxially stretched film.
[0040] Examples of the heat setting method include known methods such as a method of blowing hot air, a method of irradiating infrared rays, a method of irradiating microwaves, etc. Among these, the method of blowing hot air is preferred because it can heat uniformly and accurately.
[0041] The film after the heat setting treatment may be subjected to a heat relaxation treatment at the same temperature as the heat setting treatment temperature while being held by the clips. By performing the relaxation treatment, a film with a reduced thermal shrinkage rate can be obtained. The relaxation rate in the longitudinal direction is preferably 10% or less, more preferably 6% or less, and even more preferably 3% or less. The relaxation rate in the width direction is preferably 12% or less, and more preferably 6% or less. If the relaxation rate in the longitudinal direction exceeds 10% or if the relaxation rate in the width direction exceeds 12%, sagging may occur in the film, and the moisture absorption elongation rate may increase. The relaxation rate in the width direction is preferably 1% or more. If the relaxation rate in the width direction is less than 1%, it may not be possible to obtain a film with a sufficiently reduced thermal shrinkage rate.
[0042] It is preferable to cool the film after the heat setting treatment, or the film after the heat relaxation treatment, while being held by the clip, at a temperature lower than that in the heat setting treatment or heat relaxation treatment. By performing the cooling treatment, a sudden drop in temperature (rapid cooling) from the high temperature in the heat setting treatment or heat relaxation treatment to room temperature can be prevented, and the crystallinity of the obtained semi-aromatic polyamide film can be increased, and the bending rigidity can be increased. The cooling treatment temperature is preferably 60° C. or higher, and more preferably 70° C. or higher, while the cooling treatment temperature is preferably 100° C. or lower, and more preferably 90° C. or lower. The retention time is preferably 0.5 to 25 seconds, more preferably 1 to 20 seconds, and further preferably 2 to 15 seconds.
[0043] In the apparatus for producing the semi-aromatic polyamide film, it is preferable that the surfaces of the cylinder, the melting part of the barrel, the measuring part, the single tube, the filter, the T-die, etc. are treated to reduce the roughness of the surface in order to prevent the resin from stagnation. For example, a method of reducing the roughness of the surface can be mentioned, such as a method of modifying the surface with a substance having low polarity. Alternatively, a method of evaporating silicon nitride or diamond-like carbon onto the surface can be mentioned.
[0044] The obtained semi-aromatic polyamide film may be cut into a sheet or may be wound around a winding roll to form a film roll. From the viewpoint of productivity when used for various applications, it is preferable to form the film roll. When the film roll is formed, it may be slit to a desired width.
[0045] <Inorganic thin film layer (Y)> The inorganic thin film layer (Y) constituting the laminated film of the present invention is preferably composed of metals such as aluminum, silicon, titanium, zinc, zirconium, magnesium, tin, copper, iron, etc., oxides, nitrides, fluorides, sulfides, etc. of these metals, or mixtures thereof. Among these, aluminum oxide, silicon dioxide, magnesium oxide, zinc sulfide, titanium oxide, zirconium oxide, cerium oxide, or mixtures thereof are preferred, and aluminum oxide and silicon dioxide are more preferred because they have a large effect of improving the moisture absorption dimensional stability of the laminated film and a large effect of suppressing yellowing of the laminated film after heat treatment. The inorganic thin film layer may be a single layer or a laminate of two or more layers.
[0046] The inorganic thin film layer can be formed by known methods, for example, physical vapor deposition methods such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods such as CVD.
[0047] In the vacuum deposition method, metals such as aluminum, silicon, titanium, zinc, zirconium, magnesium, and cerium, as well as compounds such as aluminum oxide, silicon oxide, magnesium oxide, zinc sulfide, titanium oxide, and zirconium oxide, and mixtures thereof are used as deposition materials. Heating methods that can be used include resistance heating, induction heating, and electron beam heating. In addition, reactive deposition methods that introduce oxygen as a reactive gas, or use means such as ozone addition and ion assist may also be used.
[0048] The thickness of the inorganic thin film layer is preferably 5 nm or more, more preferably 8 nm or more, and even more preferably 10 nm or more, from the viewpoint of improving the moisture absorption dimensional stability of the laminated film and enhancing the effect of suppressing yellowing of the laminated film after heat treatment. The inorganic thin film layer preferably has a thickness of 500 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. If the inorganic thin film layer has a thickness of more than 500 nm, the bending resistance decreases and the manufacturing cost increases.
[0049] <Laminated film> The laminated film of the present invention is not particularly limited in structure as long as it has at least the base film (X) and the inorganic thin film layer (Y), but it is preferable that the inorganic thin film layer is formed on at least the first surface side of the semi-aromatic polyamide film which is the base film, and more preferably on both the first surface and the second surface. By forming it on both surfaces, not only can the moisture absorption dimensional stability and the yellowing suppression effect be improved, but also the warping of the entire laminated film can be prevented. From the viewpoint of production costs, it is preferable that the inorganic thin film layer is adjacent to the semi-aromatic polyamide film which is the base film.
[0050] The laminate film of the present invention can be produced, for example, by a method of laminating an inorganic thin film layer during the process of producing a semi-aromatic polyamide film as a base film (in-line lamination method), a method of laminating an inorganic thin film layer directly after obtaining a semi-aromatic polyamide film (post-lamination method), or a method of laminating a semi-aromatic polyamide film and a laminate film having an inorganic thin film layer.
[0051] The laminated film of the present invention may have various functional layers in addition to the base film (X) and the inorganic thin film layer (Y). The functions of the functional layers are not particularly limited, and may be general functions adopted in optical films, such as easy adhesion function, hard coat function, antistatic function, antiglare function, low reflection function, antireflection function, antifouling function, oxygen barrier function, electromagnetic wave shielding function, undercoat function, ultraviolet absorbing function, adhesive function, and hue adjustment function. When used as an LED mounting substrate, adhesion to the circuit-forming metal is required, so it is preferable that the functional layers have an easy adhesion function. The functional layer may be a layer having one type of function, or a layer having two or more types of functions. The functional layer may have multiple functions in one layer, or two or more layers each having a different function may be laminated. When two or more layers are laminated, the order of lamination is appropriately set according to the function. These layers are laminated on one or both sides of the laminate film. When laminated on both sides, the thickness, function, and lamination order of the layers laminated on each side may be the same or different.
[0052] <Physical properties of laminated film> In the present invention, the laminated film when heat-treated under the conditions of 250° C.×5 minutes has a yellowness index (YI) measured according to JIS K 7373. B ) is 5.50 or less, preferably 3.20 or less, more preferably 2.90 or less, and even more preferably 2.80 or less. The laminated film has the above yellowness index (YI B ) is 5.50 or less, yellowing after soldering can be suppressed. The YI value and the yellowness before heat treatment at 250°C for 5 minutes (YI A Yellowing index (YI) is expressed as a ratio of B / YI A ) is 1.60 or less, preferably 1.50 or less, and more preferably 1.40 or less.
[0053] The laminated film of the present invention has a moisture absorption elongation rate in the longitudinal direction and the width direction of the film, which is measured when the humidity environment is changed from 23°C x 50% RH to 23°C x 90% RH, of preferably 0.2% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. When the moisture absorption elongation rate of the laminated film is 0.2% or less, the moisture absorption dimensional change in each process when used as an LED mounting board can be reduced. In particular, it becomes possible to further prevent positional deviation when mounting solder after circuit formation.
[0054] The laminated film of the present invention has a water vapor permeability of 5.5 g / (m2) at 40°C x 90% RH as measured in accordance with JIS K7129-1. 2 d) or less, and 5.0 g / (m 2 d) or less, and more preferably 3.0 g / (m 2 d) or less, and more preferably 2.0 g / (m 2 d) or less, and more preferably 1.0 g / (m 2 ·d) It is most preferable that it is less than or equal to: The laminated film has a water vapor permeability of 5.5g / (m 2 By satisfying d) or less, moisture absorption during each process when used as an LED mounting substrate can be reduced. In particular, it is possible to prevent misalignment when mounting solder after circuit formation.
[0055] <Applications of laminated film> The laminated film of the present invention has a yellowness index (YI) of 1.0 or less when heat-treated at 250° C. for 5 minutes. B ) is 5.50 or less, yellowing after heat treatment is suppressed, heat resistance is excellent, and dimensional stability after moisture absorption is excellent, so it is suitable for use in applications requiring heat resistance and high dimensional stability during processing. Specific examples include display applications, flexible printed circuit board applications, solar cell substrates, copper-clad laminates (FCCL), transparent LED display substrates, ITO substrates, etc. In particular, because it makes it possible to prevent misalignment when mounting solder after circuit formation, it is ideally used as an LED mounting substrate for flexible LED displays, optical substrates for organic electroluminescence (EL) and the like, flexible printed wiring boards, flexible flat cables and other electronic substrate materials, as well as coverlay films for flexible printed wiring.
[0056] A copper-clad laminate obtained by laminating copper to the laminate film of the present invention is suitably used as an LED mounting board, a flexible printed circuit board, and the like. The method of laminating copper on the laminated film of the present invention is not particularly limited, and examples thereof include a lamination method using copper foil, a sputtering method, and an electroless plating method. Examples of the copper foil used in the lamination method include electrolytic copper foil and rolled copper foil. As the seed layer used in the sputtering method or the electroless plating method, metals such as nickel and chromium, or alloys of these metals can be used.
[0057] An example of the configuration of an LED display using the laminated film of the present invention is shown below. LED element / circuit / (laminated film of the present invention) Coverlay / adhesive layer / LED element / circuit / (laminated film of the present invention) Hard cover layer / LED element / circuit / (laminate film of the present invention) / hard cover layer EXAMPLES
[0058] The present invention will be specifically described below with reference to examples. 1. Evaluation method (1) Intrinsic viscosity of semi-aromatic polyamide resin The intrinsic viscosity (ηinh) of the resin at concentrations of 0.05, 0.1, 0.2, and 0.4 g / dL in concentrated sulfuric acid at 30°C was calculated using the following formula, and the value extrapolated to a concentration of 0 was taken as the limiting viscosity [η]. ηinh=[ln(t1 / t0)] / c (In the formula, ηinh is the intrinsic viscosity (dL / g), t0 is the flow time of the solvent (seconds), t1 is the flow time of the resin solution (seconds), and c is the concentration of the resin in the solution (g / dL).)
[0059] (2) Melting point and glass transition temperature of semi-aromatic polyamide resin Using a differential scanning calorimeter (PerkinElmer DSC-7), the semi-aromatic polyamide resin was heated from 20°C to 350°C at 10°C / min under a nitrogen atmosphere and held for 5 minutes (1st scan), then cooled from 350°C to 20°C at 100°C / min and held for 5 minutes. The glass transition temperature during the process of heating again from 20°C to 350°C at 10°C / min (2nd scan) was taken as Tg of the semi-aromatic polyamide resin. Similarly, the peak top temperature of the crystal melting peak observed in the 2nd scan was taken as Tm.
[0060] (3) Yellowness index (YI) of laminated film Using a test piece (width 50 mm × length 50 mm) cut out from the laminated film, the yellowness index (YI) was calculated according to the following formula in accordance with JIS K 7373 using a spectrophotometer / colorimeter SE 6000 manufactured by Nippon Denshoku Industries Co., Ltd. Yellowness index (YI)=100(1.2985X-1.1335Z) / Y The yellowness of the laminated film that was heat-treated at 250℃ for 5 minutes using ETAC HISPEC HT350 was measured as YI. B The yellowness of the laminated film that was not heat-treated at 250°C for 5 minutes was calculated as YI. A The yellowness ratio (YI B / YI A ) was calculated and evaluated as the yellowing degree.
[0061] (4) Moisture absorption elongation rate of laminated film The laminated film was left for 2 days in an environment with a temperature of 23°C and a relative humidity of 50%, and then a test piece (200 mm wide x 300 mm long) was cut out and marked in the longitudinal and transverse directions with a gauge length of 100 mm. After moisture absorption treatment for 2 days in an environment with a temperature of 23°C and a relative humidity of 90%, the gauge lengths in the longitudinal and transverse directions were measured, and the moisture absorption elongation of the test piece in the longitudinal and transverse directions was calculated by the following formula. Moisture absorption elongation rate (%) = [{length after moisture absorption treatment - original length} / original length] x 100
[0062] (5) Water vapor permeability of laminated film Measurements were performed using a water vapor barrier tester (PERMATRAN-W 3 / 33 manufactured by Mocon) in accordance with JIS K7129-1 under an atmosphere of temperature 40°C and relative humidity 90%.
[0063] 2. Raw Materials (1) Semi-aromatic polyamide resin Semi-aromatic polyamide resin A: The following preparations were used: 3289 parts by mass of terephthalic acid (TA), 2533 parts by mass of 1,9-nonanediamine (NDA), 633 parts by mass of 2-methyl-1,8-octanediamine (MODA), 48.9 parts by mass of benzoic acid (BA), 6.5 parts by mass of sodium hypophosphite monohydrate (0.1% by mass relative to the total of the four polyamide raw materials) and 2200 parts by mass of distilled water were placed in a reactor and substituted with nitrogen. The molar ratio of these raw materials (TA / BA / NDA / MODA) was 99 / 2 / 80 / 20. The contents of the reactor were stirred at 100°C for 30 minutes, and then the internal temperature was raised to 210°C over 2 hours. At this time, the internal pressure of the reactor was 2.12 MPa (22 kg / cm 2 The reaction was continued for 1 hour, after which the temperature was raised to 230°C and kept at 230°C for another 2 hours. The steam was gradually released and the pressure was reduced to 2.12MPa (22kg / cm 2 The reaction was carried out while maintaining the pressure at 0.98 MPa (10 kg / cm) for 30 minutes. 2 ) and reacted for another hour to obtain a prepolymer, which was then dried at 100°C under reduced pressure for 12 hours and then crushed to a size of 2 mm or less. The pulverized prepolymer was then subjected to solid-phase polymerization for 10 hours under conditions of a temperature of 230°C and a pressure of 13.3 Pa (0.1 mmHg) to obtain a polymer. This was fed to a twin-screw extruder (TEX44C manufactured by Japan Steel Works, Ltd.), melt-kneaded and extruded under conditions of a cylinder temperature of 320°C, cooled, and cut to produce pellets of semi-aromatic polyamide resin A. Semi-aromatic polyamide resin A had a melting point of 290°C, a glass transition temperature of 125°C, and an intrinsic viscosity of 1.17 dL / g.
[0064] (2) Fine particles A master chip (M1) containing 2% by mass of silica, which was prepared by the following method, was used. Master Chip (M1): 98 parts by mass of semi-aromatic polyamide resin A and 2 parts by mass of silica (manufactured by Tosoh Silica Corporation, NIPGEL AZ-204, average particle size 1.7 μm) were melt-kneaded.
[0065] (3) Hindered phenol heat stabilizer GA: 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane (Sumitomo Chemical Co., Ltd. Sumilizer GA-80, thermal decomposition temperature 392°C)
[0066] Example 1 Semi-aromatic polyamide resin A, GA, and master chip (M1) were mixed so that the amount of GA was 0.2 part by mass and the amount of silica was 0.1 part by mass per 100 parts by mass of semi-aromatic polyamide resin A. This mixture was fed into a 65 mm single-screw extruder with a cylinder temperature set at 320°C, melted, extruded into a sheet from a T-die set at 320°C, and cooled by electrostatically bonding it to a cooling roll set at a surface temperature of 40°C, obtaining a substantially unoriented unstretched film with a thickness of 650 μm. Next, the obtained unstretched film was stretched 3.0 times in the longitudinal direction under the condition of 130 ° C. with a roll-type longitudinal stretching machine, and then the ends of the film were continuously held by the clips of a flat-type stretching machine, and while both ends were held by the clips, stretching was performed in the width direction under the conditions of a preheating section temperature of 155 ° C. and a stretching section temperature of 150 ° C. The stretching conditions were a stretching strain rate of 3200% / min in the longitudinal direction and the width direction, and a stretching ratio of 3.0 times and 3.3 times in the longitudinal direction and the width direction, respectively. After stretching, a heat setting treatment was performed at 280 ° C. for 5 seconds, and a relaxation treatment was performed with a relaxation rate of 1% in the longitudinal direction and 3% in the width direction to obtain a semi-aromatic polyamide film with a thickness of 75 μm. The obtained semi-aromatic polyamide film was placed in a batch-type vacuum deposition machine, and the vacuum deposition machine was heated for 10 -4 The pressure was reduced to below Torr, 99.99% pure metallic aluminum was loaded into the crucible placed at the bottom, and the metallic aluminum was heated and evaporated, and oxygen was supplied to the vapor to cause an oxidation reaction, which was then deposited on the first surface of the film to form an aluminum oxide film with a thickness of 0.03 μm as the inorganic thin film layer (Y). An aluminum oxide film was then formed on the second surface of the semi-aromatic polyamide film using the same method, yielding a laminated film with an inorganic thin film layer (Y) of 0.03 μm / substrate film (X) of 75 μm / inorganic thin film layer (Y) of 0.03 μm.
[0067] Example 2 A semi-aromatic polyamide film was obtained in the same manner as in Example 1, and a SiO 2 A thin film layer of 30 nm thickness was formed using a vacuum deposition method using (Takaoshin Corporation, SI-507050), to obtain a laminated film of 30 nm silicon oxide / 75 μm substrate film. A thin film layer was also formed on the second surface using the same method, to obtain a laminated film of 30 nm silicon oxide layer / 75 μm substrate film / 30 nm silicon oxide layer.
[0068] Comparative Example 1 A semi-aromatic polyamide film having a thickness of 75 μm was obtained in the same manner as in Example 1. No inorganic thin film layer was laminated.
[0069] Comparative Example 2 A water-based coating agent (Sumitomo Chemical Co., Ltd., Exevier NOH1200) was applied by gravure roll coating to the first surface of the semi-aromatic polyamide film obtained in the same manner as in Example 1, and the film was dried for 30 seconds by an infrared irradiator at a temperature of 100° C. to form a resin layer having a thickness of 2 μm, and a laminated film having a resin layer of 2 μm / substrate film of 75 μm was obtained. A resin layer was also formed on the second surface by the same method to obtain a laminated film having a resin layer of 2 μm / substrate film of 75 μm / resin layer of 2 μm.
[0070] The composition and physical properties of the laminated film are shown in Table 1.
[0071] [Table 1]
[0072] The laminated films of Examples 1 and 2 had a low yellowing index (ratio of yellowing index after heat treatment to yellowing index before heat treatment) after heat treatment for 5 minutes at 250°C, and yellowing due to heat treatment was suppressed. The water vapor permeability was 5.5 g / (m 2 In particular, the laminated film of Example 1 was excellent in dimensional stability upon moisture absorption, and no solder misalignment occurred when processing the LED mounting board. The substrate film of Comparative Example 1, which does not have an inorganic thin film layer laminated thereon, showed an increase in yellowness after heat treatment at 250° C. for 5 minutes, and the degree of yellowing was high. In addition, the water vapor permeability was 5 g / (m 2 The laminated film of Comparative Example 2 in which a resin layer was laminated on a base film had a low water vapor permeability, but the yellowing degree after heat treatment at 250°C for 5 minutes was significantly high, and the heat resistance was poor.
Claims
1. A laminated film having at least a base film (X) and an inorganic thin film layer (Y), The base film (X) is a semi-aromatic polyamide film, Yellowness index (YI) when heat treated at 250°C for 5 minutes B ) is 5.50 or less, and the yellowness index (YI) before the heat treatment is A Yellowing index (YI) is expressed as a ratio to the B / YI A ) is 1.60 or less.
2. 2. The laminate film according to claim 1, characterized in that the moisture absorption elongation in the longitudinal direction and the moisture absorption elongation in the transverse direction of the laminate film, measured when the humidity environment is changed from 23°C x 50% RH to 23°C x 90% RH, are each 0.2% or less.
3. The water vapor permeability of the laminated film at 40°C x 90% RH measured in accordance with JIS K7129-1 is 5.5 g / (m 2 3. The laminated film according to claim 1, wherein the thickness is d) or less.
4. 3. The laminate film according to claim 1 or 2, characterized in that it has an inorganic thin film layer (Y) on a first surface side of the base film (X) and also has an inorganic thin film layer (Y) on a second surface side of the base film (X).
5. 3. The laminated film according to claim 1, wherein the semi-aromatic polyamide film is biaxially oriented.
6. 3. The laminate film according to claim 1, wherein the base film (X) and the inorganic thin film layer (Y) are adjacent to each other.
7. A copper-clad laminate comprising the laminate film according to claim 1 or 2.
8. An LED mounting substrate using the laminate film according to claim 1 or 2.
9. An LED display using the LED mounting board according to claim 8.
Citation Information
Patent Citations
Semiaromatic polyamide film and method for producing same
WO2020230806A1